2011
DOI: 10.1038/ng.848
|View full text |Cite
|
Sign up to set email alerts
|

Extensive and coordinated transcription of noncoding RNAs within cell-cycle promoters

Abstract: Transcription of long noncoding RNAs (lncRNAs) within gene regulatory elements can modulate gene activity in response to external stimuli, but the scope and functions of such activity are not known. Here we use an ultra-high density array that tiles the promoters of 56 cell cycle genes to interrogate 108 samples representing diverse perturbations. We identify 216 transcribed regions that encode putative lncRNAs--many with RT-PCR-validated periodic expression during the cell cycle, show altered expression in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
920
0
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,063 publications
(963 citation statements)
references
References 51 publications
11
920
0
16
Order By: Relevance
“…Likewise, the reported modes of action for this transcript class differ substantially: An emerging theme in lncRNA-mediated control of gene expression, however, seems to be the recruitment of histonemodifying complexes to specific loci in the genome to epigenetically regulate target gene transcription (Mercer and Mattick, 2013;Rinn, 2014). For several further lncRNAs, however, other functions have been reported: Some representatives act as decoys by titrating transcription factors and thus, indirectly regulate target gene transcription (Hung et al, 2011).…”
Section: Eukaryotic Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%
“…Likewise, the reported modes of action for this transcript class differ substantially: An emerging theme in lncRNA-mediated control of gene expression, however, seems to be the recruitment of histonemodifying complexes to specific loci in the genome to epigenetically regulate target gene transcription (Mercer and Mattick, 2013;Rinn, 2014). For several further lncRNAs, however, other functions have been reported: Some representatives act as decoys by titrating transcription factors and thus, indirectly regulate target gene transcription (Hung et al, 2011).…”
Section: Eukaryotic Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%
“…Other studies have inferred and tested the functional role of lincRNAs in processes such as pluripotency and p53 response pathways by associating the expression of lincRNAs with those of protein-coding genes (Guttman et al 2009;Huarte et al 2010;Loewer et al 2010;Hung et al 2011). More globally, a recent comprehensive screen identified dozens of lincRNAs required to maintain pluripotency and suggested that these lincRNAs work in trans .…”
mentioning
confidence: 99%
“…For example, several lncRNAs have been shown to interact with and modulate the activity of the chromatin modifying machinery (Rinn et al 2007;Nagano et al 2008;Pandey et al 2008;Zhao et al 2008Zhao et al , 2010Khalil et al 2009;Huarte et al 2010;Tian et al 2010;Tsai et al 2010;Guttman et al 2011;. Other lncRNAs may act as decoys in the sequestration of miRNAs (Poliseno et al 2010), transcription factors (Hung et al 2011), or other proteins (Tripathi et al 2010). Yet others may serve as precursors for the generation of sRNAs (Kapranov et al 2007;Wilusz et al 2008;Fejes-Toth et al 2009).…”
mentioning
confidence: 99%